Pentecostal prophets: experience in Old Testament perspective - Barkley, Stephen D. (Wipf & Stock, 2023)
"Prophets come in many varieties--ecstatic worshipers, inspired preachers, social justice advocates, and even political pundits. Their messages vary accordingly. The purpose of this book is to dig beneath the message to understand the how. How do modern-day prophets experience the prophetic impulse? The phenomenological study at the core of this book answers that question directly by examining the experience of Canadian Pentecostals. From there, the experience of modern-day prophets is compared with Old Testament prophets, with special attention given to Jeremiah. It turns out that prophets today share in the same experience as their Old Testament predecessors. This book can benefit three audiences. For the academy, this work provides the first phenomenological study of prophecy in Canada. For pastors, reading this book will be an exercise in empathy, placing you in the shoes of the prophets in your congregation, helping you to understand what goes on when someone prophesies. For everyday prophets, this book will affirm your connection, through Jesus, to the Old Testament prophetic tradition, enabling you to read those Old Testament books in a new experiential light." --